3D Printed Model Used as Preoperative Tool for Treating Acromioclavicular Joint Dislocation with Pre-Contoured Clavicle Hook Plate: Technical Note - Wu, Xuhua; Wang, Gang; Rong, Ke; Xia, Qingquan; Gan, Minfeng; Wen, Gen; Yin, Xiaofan; Yang, Huilin (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
Objective To introduce a new technique using real-size 3D-printed acromioclavicular joint models as preoperative tools for treating acromioclavicular (AC) joint dislocation.Methods Both the injured AC joint and the mirrored normal side AC joint are 3D printed into real-size models. A proper hook plate is selected and pre-bended to fit the normal side AC joint. The bended plate is then used to perform a reduction operation on a real-size injured AC joint model and the result is compared with the mirrored normal AC joint model to see if the reduction is accurate.Results It is easy to select and bend a clavicle hook plate to achieve an accurate reduction with the help of a 3D printing technique.Conclusion With this technique, surgeons can achieve an accurate reduction of the injured AC joint with a clavicle hook plate which might be helpful to reduce the risk of complications.
Keywords: acromioclavicular joint dislocation; clavicle hook plate; 3D printing